Covid-19 customer experiences of self-service technology across pharmacies in South Africa - Sebonkile Thaba; Lunga Jacobs; Adrien Ilumbe Laby (Cogent Social Sciences)
Using time-series data over a period of twelve months, Atlas.ti was employed to analyse the data extracted from Hello Peter, a South African online customer review and business platform, to assess Covid-19 customer reactions to e-services across South African pharmaceutical retailers. The focus was on the two largest retailers as they formed the bulk of the complaints. Multiple variables were grouped into relevant output variables. Content analysis was used as a guide in answering the research questions. Results showed that online pharmaceutical retailers had an attitude of no replies, equally ghosting customers. The study contribution is based on the understanding of customer reactions to the incidents of unacceptable online retailing services. The findings highlighted the profound implications on retailers to comprehend the importance of providing quality customer services to achieve customer satisfaction, leading to the establishment of profitable relationships, while also acknowledging that the implications were caused by the pandemic and could have been different.